2020
DOI: 10.3390/nu12113440
|View full text |Cite
|
Sign up to set email alerts
|

Protein Labelling Accuracy for UK Patients with PKU Following a Low Protein Diet

Abstract: A phenylalanine (protein)-restricted diet is the primary treatment for phenylketonuria (PKU). Patients are dependent on food protein labelling to successfully manage their condition. We evaluated the accuracy of protein labelling on packaged manufactured foods from supermarket websites for foods that may be eaten as part of a phenylalanine-restricted diet. Protein labelling information was evaluated for 462 food items (“free from”, n = 159, regular, n = 303), divided into 16 food groups using supermarket websi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 11 publications
(14 reference statements)
0
4
0
Order By: Relevance
“…Several respondents were frustrated that some potentially suitable instant dessert mixes and dried cereals had a protein content given on the food analysis after manufacturers had assumed they would be reconstituted/prepared with added cow’s milk or egg, rendering the products unsuitable for people with PKU; no data were provided about the protein content of the dry products as purchased. There were many examples of ice creams that gave protein content for volume (in millilitres) rather than weight, and prepackaged foods that only gave a protein content of <0.5 g/100 g. Some commented that it would make a ‘massive difference’ if food labelling was clearer as there would be more foods that could be consumed, that the ‘confusing protein labelling made it very hard when choosing suitable foods in the supermarket’, and ‘the problems of interpreting protein labelling will not help my son become independent.’ These issues were also identified by Kravela et al 2020, who examined the accuracy of protein analysis from supermarket websites [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several respondents were frustrated that some potentially suitable instant dessert mixes and dried cereals had a protein content given on the food analysis after manufacturers had assumed they would be reconstituted/prepared with added cow’s milk or egg, rendering the products unsuitable for people with PKU; no data were provided about the protein content of the dry products as purchased. There were many examples of ice creams that gave protein content for volume (in millilitres) rather than weight, and prepackaged foods that only gave a protein content of <0.5 g/100 g. Some commented that it would make a ‘massive difference’ if food labelling was clearer as there would be more foods that could be consumed, that the ‘confusing protein labelling made it very hard when choosing suitable foods in the supermarket’, and ‘the problems of interpreting protein labelling will not help my son become independent.’ These issues were also identified by Kravela et al 2020, who examined the accuracy of protein analysis from supermarket websites [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…The questionnaire was divided into 3 sections. Section 1 collected information on patient age, sex, type of supermarket they commonly shopped at, and ease of calculating protein exchanges from food analysis labels for known problems previously identified [ 5 ].…”
Section: Methodsmentioning
confidence: 99%
“…Some protein substitutes such as CGMP-AA contain Phe which may complicate gaining acceptable blood Phe control in children [ 7 ]. Persistent consumer pressure from the food industry and busy working adult lives has led to increased dependence on processed foods which are commonly not low in Phe or may have unreliable protein labelling information [ 25 ]. In addition, societal efforts to reduce the sugar content of foods has also led to sugar replacement by artificial sweeteners such as aspartame, another unquantified source of Phe [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, incomplete information may lead to the miscalculation of natural protein intake. Previous studies have also shown a high rate (>50%) of protein-labelling errors (e.g., unclear, misleading, inaccurate, or incomplete information) affecting interpretation of protein content of packaged manufactured foods on supermarket websites [34]. Ninety per cent of patients with PKU or their caregivers reported that they experienced problems with food labelling e.g., difficulties with interpreting food protein exchanges from food labels or labels containing misleading or confusing information [35].…”
Section: Introductionmentioning
confidence: 99%